Synthesis of spirocyclopropanes via iodine-promoted bimolecular cyclization of 2-benzylidene 1, 3-indandiones. Issue 24 (17th December 2022) - He, Zeng-Yang; Ning, Yong; Zhao, Yu-Fei; Diao, Hong-Lin; Zou, Peng; Wang, Wen-Bin; Shu, Jun-Sheng; Xu, Hui
Abstract: A novel and efficient iodine-promoted bimolecular annulation of 2-benzylidene 1, 3-indandiones has been developed. Following this protocol, a series of spirocyclopropane derivatives were furnished in good to excellent yields. The present protocol features mild conditions, short reaction time, high efficiency, good chemoselectivity and remarkable functional group tolerance. Graphical Abstract: UF0001